1991
DOI: 10.1016/0378-1097(91)90115-q
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of Chlamydia pneumoniae in cell culture

Abstract: The electron microscopic appearance of Chlamydia pneumoniae elementary bodies with pear-shaped, loose outer membrane has been suggested as one criterion of its classification as a new chlamydial species. The study of the original strain TW 183 in LCL 929 and HL cells and a low-passage isolate of Kajaani-6 isolate in HL cells revealed spherical compact elementary bodies common to other chlamydia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…Carter et a1.22 demonstrated that the morphology of EBs of C. pneumoniae IOL-207 also appeared round in thin sections and were indistinguishable from those of the C. trachomatis and C. psittaci. Similarly, Popov et al 23 demonstrated round EBs in thin sections of C. pneumoniae Kajaani-6. These results, together with those presented here, strongly suggest that the " pear-shaped" profiles of EBs in thin sections are not common in C. pneumoniae and that the pear-shape is not a morphological criterion for recognising C. pneumoniae.…”
Section: Discussionmentioning
confidence: 82%
“…Carter et a1.22 demonstrated that the morphology of EBs of C. pneumoniae IOL-207 also appeared round in thin sections and were indistinguishable from those of the C. trachomatis and C. psittaci. Similarly, Popov et al 23 demonstrated round EBs in thin sections of C. pneumoniae Kajaani-6. These results, together with those presented here, strongly suggest that the " pear-shaped" profiles of EBs in thin sections are not common in C. pneumoniae and that the pear-shape is not a morphological criterion for recognising C. pneumoniae.…”
Section: Discussionmentioning
confidence: 82%
“…Other differences between N16 and TWAR are that N16 contains a plasmid and has normal EB morphology (Wills et al, 1990) whereas TWAR EBs were originally described as pear-shaped (Grayston et al, 19893). However not all TWAR isolates have abnormal EB morphology (Carter et al, 1991 ;Popov et al, 1991) and the presence or absence of a plasmid is not a reliable indicator of species. Studies on the plasmid of N16 (pCpnE) showed that it is similar in size (7.5 kb) and organization to the plasmids found in C. psittaci and C. trachomatis but that it has a unique restriction profile (Lusher et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…known that not all TWAR isolates have pear-shaped EBs (Carter et al, 1991 ;Popov et al, 1991). All isolates recognized in 1989 were from humans and they comprised a single strain that was called W A R .…”
Section: Introductionmentioning
confidence: 99%
“…The description of biovar TWAR is identical to the description of the prototypical TWAR serovar (Grayston et al, 1989), except that biovar TWAR EBs may have either of two distinct ultrastructural morphologies : the prototypical pear-shaped EB (Grayston et al, 1989) or the classic coccoid morphology of the Chlamydiaceae spp. (Carter et al, 1991 ;Miyashita et al, 1993;Popov et al, 1991). The name TWAR was formed by merging the first two letters of isolates TW-183 and AR-39 (Grayston et al, 1989).…”
Section: Description Of Chlamydia Suis Sp Novmentioning
confidence: 99%